The India-US Security and Defense Cooperation under Narendra Modi: Challenges and Assessments - Quach Thi, Hue; Le Thi, Hang Nga; Nguyen Thi, Oanh (Journal of Liberty and International Affairs (Bitola), 2024)
This article studied the reality of India-US security-defense cooperation during the period under Narendra Modi’s leadership in India. The article employed realism, liberalism, and constructivism to analyze how India and the US strengthened their security and defense partnership. Research results found that, under N. Modi’s leadership since 2014, India-US security and defense cooperation changed significantly in quantity and quality. The article concluded that security and defense became important pillars of India-US relations. It was deepened and broadened as well as became more comprehensive. India became the US’s “major defense partner”. Despite the solid security-defense cooperation with the US, India could not become the US’s ally. On the other hand, “strategic autonomy” became a prominent feature of India’s foreign policy under N. Modi.